Impacts of Information Quality and Quantity on Airbnb Users Intention to Adopt Information - Kumar, Kavigtha Mohan (Journal of Entrepreneurship, Business and Economics, 2024)
This study aims to investigate the impacts of information quantity and quality on Airbnb users’ intention to adopt information by considering trust, perceived usefulness, and attitude towards online reviews as endogenous factors. Data were collected from 202 individuals and were analysed using the partial least squares technique. The results showed that information quantity, information completeness, information relevance, information value-added, and information understandability have a positive effect on users’ trust. Furthermore, information relevance and information understandability were only factors that have a positive effect on users’ perceived usefulness. In addition, users’ trust, perceived usefulness, and attitude towards online reviews have a positive effect on information adoption. Understanding the key drivers of users’ intention to adopt information is crucial for managers of peer-to-peer accommodation service providers. Research paper Keywords: Information Quantity; Information Quality; Trust, Perceived Usefulness; Attitude towards Online Reviews; Airbnb; Information Adoption Reference to this paper should be made as follows: Kumar, K. M. (2023). Impacts of Information Quality and Quantity on Airbnb Users Intention to Adopt Information. Journal of Entrepreneurship, Business and Economics , 11 (2), 168–200.